Young people as visual culture producers : similarities and differences between their experiences inside and outside school - Vida, María Reyes González (2017)
This article presents a case-study which examines the contributions by two young people with respect to their experiences in Art Education classes, contrasting them with their experiences as visual culture producers outside the class. To do so, it is identified the knowledge they acquire outside school which serves as a base for their creations, it is explored the relationships between this knowledge and school-knowledge, and it is analyzed cases that generate contradictions. The article encourages us to ask what we can learn from their ways of learning